An empirical study of the effects of peer intelligent agent instructional strategies on EFL university students’ oral English learning performance, cognitive load, learning anxiety and technology acceptance - Gang Yang, Yudie Rong, Zhuocen Zou, Xinya Fang, Manna Yang and Qunfang Zeng (Educational Technology & Society, 2025)
For EFL students, improving oral expression is a challenging task. Therefore, this study proposes peer intelligent agent instructional strategies (PIA-IS) and explores the effects of this strategy on students’ oral English learning performance, cognitive load, learning anxiety, and technology acceptance. A quasi-experiment was conducted at a university in Zhejiang Province, China. The oral English learning activities lasted for nine weeks, with in-depth interviews with the experimental group at the end of the activities. The study showed that PIA-IS significantly improved students’ oral learning performance, enhanced oral expression integrity and accuracy, and reduced cognitive load and learning anxiety. The interviews also showed that students were satisfied with the strategy. In addition, the results of hierarchical regression analysis revealed that technology acceptance predicted oral learning performance. In short, this study provides an innovative case for EFL students to utilize smart technology to enhance oral English learning.